2019
DOI: 10.1177/0275074019869376
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Linkages Between Entrepreneurial Orientation and Local Government Sustainability Performance

Abstract: Linking strategic management to performance has been called essential for public managers to confront pernicious environmental and community problems in the 21st century. This article examines the role that an organization’s entrepreneurial orientation (EO) plays in the linkages between organizational capacities, strategies, and perceived performance. An EO is considered a key driver of a public organization’s willingness to engage in risk taking, innovation, and proactivity aimed at enhancing organizational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 70 publications
0
33
0
2
Order By: Relevance
“…Launched in response to the Great Recession, the program produced a net job gain of 62,902 job years, avoided 25.7 million metric tons of carbon emissions, and led to US$5.2 billion in total cumulative savings on energy bills (U.S. Department of Energy [U.S. DOE], 2015). It also helped hundreds of local governments take initial steps into sustainability through hiring staff and accruing expertise (Deslatte & Swann, 2020;Terman & Feiock, 2015). Despite this, research on the program found that local governments generally did a weak job of communicating these gains (Deslatte, 2020a).…”
Section: Discussion and Conclusion: Speaking Truth To Power And Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Launched in response to the Great Recession, the program produced a net job gain of 62,902 job years, avoided 25.7 million metric tons of carbon emissions, and led to US$5.2 billion in total cumulative savings on energy bills (U.S. Department of Energy [U.S. DOE], 2015). It also helped hundreds of local governments take initial steps into sustainability through hiring staff and accruing expertise (Deslatte & Swann, 2020;Terman & Feiock, 2015). Despite this, research on the program found that local governments generally did a weak job of communicating these gains (Deslatte, 2020a).…”
Section: Discussion and Conclusion: Speaking Truth To Power And Peoplementioning
confidence: 99%
“…Questions about whether our federal system is up to the challenge are only going to grow louder as these threats multiply (Adolph et al, 2020; Haffajee & Mello, 2020; Perez & Ross, 2020b). Although thousands of local governments around the world, and hundreds within the United States, have started engaging in climate action, resilience or sustainability planning (Deslatte & Swann, 2020; Hawkins et al, 2016; Swann & Deslatte, 2019; Yi et al, 2017), hardly any of them attempts to identify social vulnerabilities within their jurisdictions. This is despite readily available tools such as the CDC’s Social Vulnerability Index.…”
Section: Discussion and Conclusion: Speaking Truth To Power And Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…To discuss much more research work that is stressed obviously on changes in the economy, which is unambiguously significant for two specific motives. By employing the quantitative methods, Deslatte and Swann (2020) found the significant effect of environmental factors (political and administrative capacities) on EO. Further, the strategic activities of performance information use, venturing as well as inter-organizational collaboration mediate the relationship between perceived sustainability performance and EO.…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…In government sustainability, performance represents a complex notion [98][99][100] and is thus difficult to assess. Public entities can develop entrepreneurial orientation for improving sustainability behavior by use of capacity-building and performance management.…”
Section: Sustainability Behavior Of Urban Systemsmentioning
confidence: 99%